2003
DOI: 10.1074/jbc.m304761200
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous Polyposis Coli (APC)-independent Regulation of β-Catenin Degradation via a Retinoid X Receptor-mediated Pathway

Abstract: ␤-catenin is a component of stable cell adherent complexes whereas its free form functions as a transcription factor that regulate genes involved in oncogenesis and metastasis. Free ␤-catenin is eliminated by two adenomatous polyposis coli (APC)-dependent proteasomal degradation pathways regulated by glycogen synthase kinase 3␤ (GSK3␤) or p53-inducible Siah-1. Dysregulation of ␤-catenin turnover consequent to mutations in critical genes of the APC-dependent pathways is implicated in cancers such as colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
147
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 39 publications
(59 reference statements)
11
147
0
1
Order By: Relevance
“…A similar mechanism might be activated following stimulation of PPAR␥, because the PPAR␥2-mediated pathway of ␤-catenin degradation also involved the N-terminal (1-131 amino acids) fragment of ␤-catenin. Proteasome-mediated degradation of PPAR␥ was shown to be independent of the transcriptional activity of the receptor and was dependent upon the activation function 2 (AF2) domain (69) as was also reported in the case of RXR-mediated ␤-catenin degradation (52). It is still unclear whether the same domain of PPAR␥2 was involved in mediating ␤-catenin degradation.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A similar mechanism might be activated following stimulation of PPAR␥, because the PPAR␥2-mediated pathway of ␤-catenin degradation also involved the N-terminal (1-131 amino acids) fragment of ␤-catenin. Proteasome-mediated degradation of PPAR␥ was shown to be independent of the transcriptional activity of the receptor and was dependent upon the activation function 2 (AF2) domain (69) as was also reported in the case of RXR-mediated ␤-catenin degradation (52). It is still unclear whether the same domain of PPAR␥2 was involved in mediating ␤-catenin degradation.…”
Section: Discussionmentioning
confidence: 88%
“…It is thus possible that PPAR␥ stimulation leads to the activation of a novel proteasomal pathway, which is capable of degrading proteins involved in regulating important cellular events (example: growth and differentiation). In a very recent study a similar novel mechanism of ␤-catenin degradation has been reported to be activated by the retinoid X receptor (RXR) (52). Additionally, studies have shown that suppression of ␤-catenin-mediated signaling via nuclear recepassays were performed as in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RXR␣ binds insulinlike growth factor-binding protein-3 and is necessary for the induction of apoptosis by insulin-like growth factor-binding protein-3 or RXR agonists in cancer cells (18). We have shown that RXR agonists affect the proliferation of cells by promoting interaction of RXR␣ with ␤-catenin and the degradation of both of these molecules (19). The variety of roles that RXRs can play in regulating cell survival leads to the possibility that tumor cells may circumvent RXR-driven apoptosis.…”
mentioning
confidence: 99%